Ten recommendations for scanning foraminifera by X-ray computed tomography - A. Searle-Barnes; A. Brombacher; A. Brombacher; O. Katsamenis; O. Katsamenis; K. Rankin; M. Mavrogordato; T. Ezard (Journal of Micropalaeontology)
Marine sediment cores uniquely provide a temporally high-resolution and well-preserved archive of foraminifera fossils, which are essential for understanding environmental, ecological, and evolutionary dynamics over geological timescales. Foraminifera preserve their entire ontogeny in their fossilized shells, and much of this life history remains hidden from view under a light microscope. X-ray microfocus computed tomography (μCT) imaging of individual foraminifera reveals internal chambers and pores that are traditionally hidden from view. Their volume, shape, and growth form foundations of oceanographic and environmental research.